BANK REGULATION (Banking & Financial Services Policy Report, 2022)
In December 2021, members of the Senate Banking Committee Companies asked the Bureau to review the BNPL market and take action to protect consumers against products that pose risks, expressing concern that companies that are not subject to banking oversight can offer products with hidden fees and encourage consumers to take on debt they can't afford. What is the merchant experience? * What perspectives do regulators and attorneys general have with respect to BNPL products? * Are there ways in which the BNPL market can be improved? FFIEC Proposes Amending Temporary Waiver Proceedings The Appraisal Subcommittee (ASC) of the Federal Financial Institutions Examination Council has released a Notice of proposed rulemaking to amend existing rules of practice and procedure governing temporary waiver proceedings, which were promulgated in 1992 pursuant to Title XI of the Financial Institutions Reform, Recovery, and Enforcement Act of 1989, as amended. Existing Rules Under the existing rules of practice and procedure, when ASC receives a request from a State appraiser regulatory agency that meets the requirements set forth in 12 CFR 1102.2, including a written duly authorized determination that there is a scarcity of certified or licensed appraisers leading to significant delays in obtaining appraisals in FRTs, the request is published in the Federal Register for comment. Fed Takes "First Step" in Considering Digital Coin The Federal Reserve Board opened public talks on a Central Bank Digital Currency (CBDC) with its publication of a report on January 20 titled, "Money and Payments: The U.S. Dollar in the Age of Digital Transformation," along with a call for public response to over 20 questions relating to the possibility of a public cryptocurrency.